2018
DOI: 10.1075/ijcl.16135.lei
|View full text |Cite
|
Sign up to set email alerts
|

The academic English collocation list

Abstract: The use of collocations plays an important role for the proficiency of ESL/EFL learners. Hence, educators and researchers have long tried to identify collocations typical of either academic or general English and the challenges involved in learning them. This paper proposes a comprehensive and type-balanced academic English collocation list (AECL). AECL is based on a large corpus of academic English and was created to cover the types of collocations that will be most useful to ESL/EFL learners. AECL is the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 32 publications
0
67
0
2
Order By: Relevance
“…The selected words are sufficiently international and typically found across academic contexts (e.g. Frankenberg-Garcia, 2018; Lei and Liu, 2018).…”
Section: The Studymentioning
confidence: 99%
“…The selected words are sufficiently international and typically found across academic contexts (e.g. Frankenberg-Garcia, 2018; Lei and Liu, 2018).…”
Section: The Studymentioning
confidence: 99%
“…MI measures the strength of association between pairs of words. The most commonly used threshold is 3 to indicate a meaningful relationship (Lei & Liu, 2018). However, recent studies that tested frequency-based methods to identify collocations suggested that MI scores higher than 3 result in psychologically real collocates (Durrant & Doherty, 2010).…”
Section: Collocation Analysismentioning
confidence: 99%
“…MI scores tend to give undue weight to low frequency words and eliminate words that frequently co-occur with many words (e.g. the) (Lei & Liu, 2018). Therefore, a minimum number of co-occurrence threshold was set at 5 within 4 words to the left or right of the EUWL word (Walker, 2011).…”
Section: Collocation Analysismentioning
confidence: 99%
“…This study adopts a corpus-driven approach (see Esfandiari & Barbary, 2017;Lei & Liu, 2018), in the sense that the data is approached with no prior assumptions (Tognini-Bonelli, 2001). Tognini-Bonelli (2001, p. 86) argues that "the unexpectedness of the findings derived from corpus evidence leads to the conclusion that intuition is not comprehensively reliable as a source of information about language."…”
Section: Introductionmentioning
confidence: 99%